(untitled) (Research, Society and Development, 2019)
The present study aims to describe the nutritional profile of the elderly hospitalized in a public hospital in the city of Caxias, Maranhão. This is an experience report of the practical experience of the curricular internship in Clinical Nutrition of students of the UniFACEMA Nutrition course, developed in a public hospital located in the city of Caxias, Maranhão, in the first half of 2018. The variables gender , age, clinical and nutritional diagnosis through body mass index and food habits and lifestyle variables. As results, 30 patients, of both sexes, aged 60-84 years (68.1 ± 5.82) were evaluated. Of these, 60.0% are married or are in a stable union, 86.7% have a low level of schooling and 76.6% of the elderly have a family retirement income. The nutritional profile revealed prevalence of eating disorder (40.0% - malnourished and 26.7% - obese). The study points to the high frequency of eating disorder, such as malnutrition and obesity. We suggest further studies in the area, considering the importance of early stopping of eating disorder in hospitalized elderly patients.